Focusing on the recent progress of tea polyphenol chemistry and perspectives - Shiming Li; Liang Zhang; Xiaochun Wan; Jianfeng Zhan; Chi-Tang Ho (Food Science and Human Wellness)
ABSTRACT: Myriad evidence attests to the health-promoting benefits of tea drinking. While there are multiple factors of tea influencing the effective biological properties, tea polyphenols are the most significant and valuable components. The chemical characterization and physical characteristics of tea polyphenols have been comprehensively studied over the previous years. Still the emergence of new chemistry in tea, particularly the property of scavenging reactive carbonyl species (RCS) and the newly discovered flavoalkaloid compounds, has drawn increasing attention. In this review, we summarize recent findings of a new class of compounds in tea - flavonoid alkaloids (flavoalkaloids), which exist in fresh tea leaves and can be generated during the process of post-harvesting, and also postulate the formation mechanism of flavoalkaloids between catechins and theanine-derived Strecker aldehyde. Additionally, we detail the up-to-date research results of tea polyphenols regarding their ability to trap RCS and their in vivo aminated metabolites to suppress advanced glycation ends products (AGEs). We further raise questions to be addressed in the near future, including the synthetic pathways for the generation of flavoalkaloids and AGEs in fresh tea leaves before processing and the concentrations of tea polyphenols that affect their RCS scavenging capability due to their pro-oxidant nature. More intensive research is warranted to elucidate the mechanisms of action underlying the biological activity of flavoalkaloids and the pharmacological application of tea polyphenols in scavenging RCS and impeding detrimental AGEs.